Groundwater-dependent ecosystems and the dangers of groundwater overdraft: a review and an Australian perspective - Nevill, J.; Hancock, P.; Murray, B.; Ponder, W.; Humphreys, W.; Phillips, M.; Groom, Philip (Surrey Beatty and Sons, 2010)
In many parts of the world, access to groundwater is needed for domestic, agricultural and industrial uses, and global groundwater exploitation continues to increase. The significance of groundwater in maintaining the health of rivers, streams, wetlands and associated vegetation is often underestimated or ignored, resulting in a lack of scrutiny of groundwater policy and management. It is essential that management of groundwater resources considers the needs of natural ecosystems, including subterranean. We review the limited Australian literature on the ecological impacts of groundwater overdraft and place Australian information within an international context, focusing on lentic, lotic, stygobitic and hyporheic communities as well as riparian and phreatophytic vegetation, and some coastal marine ecosystems. Groundwater overdraft, defined as abstracting groundwater at a rate which prejudices ecosystem or anthropocentric values, can substantially impact natural communities which depend, exclusively or seasonally, on groundwater. Overdraft damage is often underestimated, is sometimes irreversible, and may occur over time scales at variance to those used by water management agencies in modelling, planning and regulation. Given the dangers of groundwater overdraft, we discuss policy implications in the light of the precautionary principle, and make recommendations aimed at promoting the conservation of groundwater-dependent ecosystems within a sustainable use context.